Plan de negocios para la creación de un Centro de Capacitación de Educación Financiera en la ciudad de Quito - Crespo Espinoza, Ángel Fabricio (2020)
The Business Plan for the creation of a Financial Education Training Center arises from the need for members of the Cooperatives of Savings and Credit of the city of Quito to be trained in the administration of personal finances, have the capacity and ability to improve their economic situation with proper management of their economic resources. A detailed analysis of the external environments that may affect the implementation of this project was carried out, finding more opportunities than threats, such as the legal aspect, growing industry, unsatisfied demand as there are few financial education training centers. According to the client analysis chapter, there is a need to train with qualified instructors who have experience and expertise in the financial field. In the marketing plan, the company will implement the specialty competitive strategy, since the training center will be dedicated exclusively to teaching personal finance, applying this strategy in the marketing mix. Regarding the operational structure, the center will establish itself in its value chain and the policies implemented by the Shareholders and Management. The Financial Evaluation demonstrates the viability and feasibility of the project through positive indicators over time, allowing an adequate profitability for its shareholders.